Swoistość procedury wyboru operatora wyznaczonego a funkcja informacyjna prawa - Szkudlarek, Piotr (Kwartalnik Prawa Publicznego, 2016)
In order to observe the time limit, a party to proceedings must dispatch correspondence through a designated operator. The article analyses ways to obtain information about which postal operator is a designated operator. It also presents de lege ferenda conclusions as well as practical comments for public authorities.